1984
DOI: 10.1007/bf01032600
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of metastatic spread and growth of tumor cells in mice with depressed natural killer activity by anti-asialo GMl antibody or anticancer agents

Abstract: The mechanism of artificial and spontaneous metastases of tumor was analyzed in B16 melanoma cells and C57BL/6 mice by using anti-asialo GM1 antibody and anticancer agents. Single administrations of 500 micrograms anti-asialo GM1 antibody resulted in significantly decreased NK activity in spleen cells of C57BL/6 mice, lasting 10 days from the day following administration. Treatment with anti-asialo GM1 antibody never decreased the function of T lymphocytes measured by blastogenesis with phytohemagglutinin or T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…NK cells which play an important role in nonspecific immunosurveillance, also inhibit the metastatic process in its early stages [27,28]. Thus it can be postulated that although intraportal chemotherapy is advocated to prevent hepatic metastases, it may also exert an unfavorable influence on immunological activity of the host, which plays an important role in preventing metastases.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells which play an important role in nonspecific immunosurveillance, also inhibit the metastatic process in its early stages [27,28]. Thus it can be postulated that although intraportal chemotherapy is advocated to prevent hepatic metastases, it may also exert an unfavorable influence on immunological activity of the host, which plays an important role in preventing metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Role of NK cells for melanoma metastasis in WT and Nox2-KO mice NK-cell function is reportedly critical to limit lung metastasis in experimental models of murine melanoma (23,28). To define the role of NK cells in the context of NOX2 inhibition, WT and Nox2-KO mice were depleted of NK cells by anti-NK1.1 antibody treatment prior to melanoma cell inoculation.…”
Section: Systemic Treatment With Hdc Did Not Affect Metastasis In Gr1mentioning
confidence: 99%
“…Lundy et al (26) reported that perioperative immunosuppression could promote the growth of micrometastases. Saijo et al (8) demonstrated that the suppression of NK cell activity by MMC enhanced the growth of experimental pulmonary and liver metastases in mice. Our results suggest that MMC given by bolus injection may be contraindicated as postoperative adjuvant chemotherapy because of its adverse effect on NK cell activity.…”
Section: Days Aftersurgery 21mentioning
confidence: 99%
“…The drug most commonly used in Japan is mitomycin C (MMC) (2); the maximum effective dose of MMC suppresses natural killer (NK) cell activity and pretreatment with Received January 12, 1998; accepted March 23, 1998 For reprints and all correspondence: Koichi Ishikawa, Department of Surgery I, Oita Medical University, 1-1 Idaigaoka, Hasama-machi, Oita 879-5593, Japan Abbreviations: CDDP, cisplatin; 5-FU, 5-fluorouracil; MMC, mitomycin C; NK, natural killer; pre-op, preoperative; POD, postoperative days; PBS, phosphate-buffered saline; PBMC, peripheral blood mononuclear cells; FCS, fetal calf serum; Err ratio, effector-to-target ratio this drug enhances the growth ofthe experimental metastases (8). Cisplatin (CDDP) and 5-fluorouracil (5-FU) are among the major agents which have been tested in clinical trials (2,9), and recently attention has turned to the combination therapy of low-dose CDDP-5-FU because of biochemical modulation (10,11).…”
Section: Introductionmentioning
confidence: 99%